Mechanical behaviour of reaction processed SiC ceramics from artificial precursor from plant. Issue 8 (June 2016) - Maity, Anwesha; Kayal, Nijhuma; Chakrabarti, Omprakash
Abstract: Mechanical behaviour of SiC ceramics synthesized from two artificial precursors from plants – coir fibreboard and bamboo pulp fibreboard – was studied and the mechanical properties – flexural strength, Young's modulus, fracture toughness and hardness – of the ceramics synthesized from the two kinds of artificial precursors were compared. The effect of processing of the artificial precursors, as reflected in the microstructure of the ceramics synthesized from them, was taken into consideration in the analysis of the mechanical property data; these data could also be possible to be explained by the empirical models of fracture mechanics. The results of the study established the possibility of application of the investigated SiC materials as structural ceramics.